Intumescent materials for heat-shielding of constructions operating under extreme conditions - Istomina, T.S.; Tiunova, T.G.; Oshchepkova, T.E.; Astaf'yeva, S.A. (Perm Federal Research Centre Journal, 2018)
Novel intumescent materials have been obtained and the properties of these materials have been thoroughly studied. The use of carbon raw materials (coal pitch, oil coking additive) as a coke- and pore-forming component was shown to be efficient. According to the results of the material testing in isothermal and dynamic modes, as well as the study of the properties of the obtained materials, one can suppose that these materials can be used for heat-shielding under extreme conditions.